PROTOCOL: Effectiveness of Sexual and Reproductive Health Blended Learning Approaches for Capacity Strengthening of Health Professionals in Low‐ and Middle‐Income Countries: A Systematic Review - Elizabeth A. Kumah; Florence Mgawadere; Alice Ladur; Zainab Suleiman; Yusupha Sanyang; Sarah A. White; Nicholas Furtado; Uzochukwu Egere; Charles Ameh (Campbell Systematic Reviews)
ABSTRACT This is the protocol for a Campbell systematic review. The objectives are as follows. The primary objective of this systematic review is to evaluate and synthesise both published and unpublished literature on the effectiveness of sexual and reproductive health blended learning approaches for capacity strengthening of healthcare practitioners in LMICs. Within this context, sexual and reproductive health interventions refer to any of the following four key interventions or services aimed at improving maternal and newborn health (Starrs et al. 2018): (a) antenatal, childbirth and postnatal care, including emergency obstetric and newborn care, (b) safe abortion services and treatment of the complications of unsafe abortion, (c) prevention and treatment of malaria, tuberculosis, HIV and other sexually transmitted infections in pregnant women and d) family planning. In this systematic review, blended learning is defined as any teaching and learning method that combines face‐to‐face learning with e‐learning or online learning. The component of face‐to‐face and online learning may include any of the components identified by Alammary (2019): (1) face‐to‐face instructor‐led, where students attend a class and an instructor presents teaching and learning materials, with little engagement from students; (2) face‐to‐face collaboration, where students work together in class, for example, in discussion groups; (3) online instructor‐led, where instruction is delivered online and facilitated by an instructor who sets the pace (e.g., virtual classrooms); (4) online collaboration, where students work together online with their peers, for example, online learning communities; and (5) online self‐paced, where students study at their own pace and time, and from their chosen location, for example, watching videos, online reading. Specifically, this systematic review will answer the following research questions: (1) What sexual and reproductive health blended learning approaches have been used in LMICs? (2) Does participating in sexual and reproductive health blended learning interventions alone (i.e., compared with no intervention) improve the effective provision of care among healthcare workers in LMICs? (3) Does participating in sexual and reproductive health blended learning interventions compared with non‐blended learning approaches (such as conventional face‐to‐face learning or pure e‐learning) facilitate the effective provision of care among healthcare workers in LMICs (measured by, e.g., self‐reports of effective maternal and neonatal care)? (4) What is the cost‐effectiveness of sexual and reproductive health blended learning compared with non‐blended learning approaches (i.e., face‐to‐face learning or e‐learning)? (5) What factors affect the effectiveness of sexual and reproductive health blended learning interventions (e.g., characteristics of participants, type of intervention, course content, setting and mode of delivery)? (6) Do sexual and reproductive health blended learning interventions targeted at healthcare practitioners working in LMICs lead to improvement in patient outcomes (e.g., reduced maternal and neonatal mortality, patient satisfaction reports)?